PENGARUH PERMAINAN BOLA BOWLING TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 4-5 TAHUN DI PAUD KUNTUM MEKAR PEKANBARU - Aprianty '; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Based on observations of researchers in early childhood Kuntum Mekar, found some symptoms or phenomena in children related to gross motor development is still low, this can be seen from fenopmena field namely 1) the existence of some children who are less able to throw in a focused until the ball can not be fixed on target. 2) lack of ability of some children in balancing the body, it ii noticeable when children throw a ball kid fell. 3) some children are less able to keep the body coordinating this is seen when the child is standing on one line and followed the line but the boy fell down and out of line, such as when the children were asked to jump over obstacles board but the boy just past the board titin to walk without jumping. 4) lack of ability of some children to run fast and focused. This research is a study with experimental approach is a study that seeks to influence specific variables other variables in strictly controlled conditions. The subject of research is PAUD Bud Bloom Pekanbaru numbering as many children as 14 children, consisting of 9 men and 5 women. Collecting data using observation and documentation. Based on the survey results revealed that 1) the ability of Motor Rough children aged 4-5 years in early childhood Blooming Bud Pekanbaru before being given treatment of the application of relatively low bowling ball game 2) gross motor ability of children aged 4-5 years in early childhood Blooming Bud Pekanbaru after being given treatment of the application of a bowling ball game has increased and is high 3) application of a bowling ball games have an impact for 19.64% of the gross motor skills of children aged 4-5 years in early childhood Blooming Bud Pekanbaru.Keywords : Bowling Ball game and Kids Rough Motoric Capabilities